Numerical Modeling of Stress Ratios in Single-Lap Adhesive Joints with Geometrical Modifications - Asep Kurnia; Ichsan Setya Putra; Hendri Syamsudin; Muhamad Giri Suada; Oktavianus Demas Priambudi (Advance Sustainable Science Engineering and Technology, 2026)
This study aims to analyze the effect of variations in aluminum strip geometry and Araldite adhesive on the mechanical strength of single lap joints. A two-dimensional numerical model was developed in Abaqus/Standard using cohesive zone elements, the Benzeggagh-Kenane (B-K) model, and a quadratic stress criterion to validate the experimental results. The results show that the developed model is capable of accurately describing the stress distribution and the effect of secondary bending moments through the ratio of normal stress to shear stress. The application of chamfer geometry to the adhesive area proved to be effective in reducing secondary bending moments and increasing joint resistance. A comparison between the experimental and numerical simulation results showed a deviation of less than 15.5%, confirming the validity of this model. This study highlights the importance of geometric optimization in improving the mechanical strength and reliability of adhesive joints.